"I won't be around forever": Understanding the decision-making experiences of adults with severe TBI and their parents. Issue 2 (3rd March 2016) - Knox, Lucy; Douglas, Jacinta M.; Bigby, Christine
Abstract : There is growing recognition of the right of all individuals, including those with cognitive impairment, to make decisions about their own lives. However, little is known about how the process of decision making is experienced after severe traumatic brain injury (TBI). This study used constructivist grounded theory to explore processes used by adults with severe TBI and their parents in making decisions about life after injury. Data consisted of 18 individual, in-depth interviews with four dyads (consisting of an individual with severe TBI and his or her parent). The overlying construct emerging from the data was a process of reimagining the future, which influenced how participants approached and participated in making decisions. In line with this construct, two central themes described processes of joint decision making within parent–adult child relationships after severe TBI over time: (1) making decisions with parental support, and (2) reducing parental involvement. These findings emphasise the complexity of supporting decision making after injury, and illustrate that both parents and their adult children with TBI use explicit and implicit strategies to facilitate increased participation in making decisions. This study also underscores the need for brain injury clinicians to consider the needs of parents who find themselves in this role.